SOCIAL MEDIA AND EFFORT TO COAX YOUNG VOTERS IN JAKARTA, INDONESIA - Astuti, Prida Ariani Ambar; Hangsing, P. (Institute of Research and Community Outreach - Petra Christian University, 2016)
Political information is often regarded as a topic that is too heavy and not appealing to young voters and this makes them become apathetic. They also considered that there was no point in participating in politics because whatever they do can not change the situation. However, these conditions change with the emergence of social media. Social Media is a new media, which have different characteristics from previous media. It also has the potential to maximize the interactivity and two-way communication that allows users to engage and participate actively. However, with the presence and advantages of social media, can this media change the interest of young voters to political information, which in turn encourages them to participate in the election? By using a survey of students in departments that are accredited 'A' in Jakarta, the research concluded that the ability to convey information, the opportunity to connect directly with the candidate, as well as the opportunity to actively participate contained in social media, had an impact on the level of interest in political information and decision-making to select a candidate for young voters in elections